THE 2015 INTER-REGIONAL SEMINARS ON RADIATION HYGIENE FOR LOCAL AGENCIES AND ORGANIZATIONS’ SPECIALISTS OF THE FEDERAL SERVICE FOR SURVEILLANCE ON CONSUMER RIGHTS PROTECTION AND HUMAN WELL-BEING - A. N. Barkovskiy; M. V. Kaduka (Радиационная гигиена)
The article is dedicated to the inter-regional seminars on ensuring population radiation safety held in 2015. Each one of the eight inter-regional centers of Federal Service for Surveillance on Consumer Rights Protection and Human Well-Being conducts such seminars once in every two years in order to render organizational, methodological and practical assistance on the issues of population radiation protection ( Inter-Regional Centers on Radiation Safety – IRC RS ) In 2015 the inter-regional seminars were conducted by the following inter-regional centers: the Central IRC RS in Moscow on March 18–19, the Southern IRC RS in Simferopol on April 21-23, the Far Eastern IRC RS in Habarovsk on May 26-28, the Siberian IRC RS in Gorno-Altaisk on September 22-24 and the Head Scientific-Methodological Center of Federal Service for Surveillance on Consumer Rights Protection and Human Well-Being (HSMC) in St. Petersburg on October 7-8.The seminar elucidated upon current issues of ensuring population radiation protection. The presentations were made by the top-notch specialists of St. Petersburg Research Institute of Radiation Hygiene after Professor P.V. Ramzaev. They expanded upon limitation of population exposure from natural, medical and technogenic ionizing radiation sources, implementation of new regulatory-methodological documents devised by the Federal Service for Surveillance on Consumer Rights Protection and Human Well-Being. They also dwelled upon state-of the-art instruments and methods of conducting radiation monitoring. Practical matters were discussed in relation to establishment of sanitary-epidemiological supervision over population radiation protection.The article highlights the issues discussed at those seminars, major challenges underscored by the participants as the result of the discussions. It provides the general evaluation and conclusions based on the seminars’ outcomes. The smooth organization of those seminars was highly appreciated. It was indicated that such seminars should carry through into the future to be held in different subject of the Russian Federation. The necessity of targeted financing of the inter-regional centers was identified with the aim of conducting sophisticated radiation monitoring in the corresponding Russian Federation Subjects. A mention was given to the importance of enhancing inter-regional centers preparedness for population radiation protection during radiation accidents.